The Influence of the Tolerance between Mechanical Components on the Accuracy of Implants Inserted with a Stereolithographic Surgical Guide: A Retrospective Clinical Study. (24th July 2013) - Cassetta, Michele; Di Mambro, Alfonso; Di Giorgio, Gianni; Stefanelli, Luigi V.; Barbato, Ersilia
Abstract Background The stereolithographic‐guided surgery system involves a sequence of diagnostic and therapeutic events, and errors can arise at different stages. In these systems, one of the potentially clinically relevant errors may be the mechanical errors caused by the bur‐guide gap due to the presence of a rotational allowance of the drills in the tubes. Purpose The purpose of this retrospective clinical study is to determine if it is possible to reduce the total error by limiting the tolerance among the mechanical components and to evaluate its clinical incidence. Materials and Methods Sixty‐six implants were inserted using the External Hex Safe® (Materialise Dental, Leuven, Belgium) system (Group A), and 71 implants were inserted using the same system with mechanical components modified to minimize the tolerance (Group B). Regarding only the angular deviation values, the t‐test was used to determine the influence of reduced tolerance among the mechanical components on the accuracy values. Results t‐Test showed that there is a statistically significant better accuracy with the modified system (Group B). Conclusions Limiting the error that originates from mechanical components, total error could be statistically significantly reduced. Mechanical error is one of the most important source of error using External Hex Safe stereolithographic surgical guide.